2015
DOI: 10.3233/nre-141193
|View full text |Cite
|
Sign up to set email alerts
|

A single blind, clinical trial to investigate the effects of a single session extracorporeal shock wave therapy on wrist flexor spasticity after stroke

Abstract: BACKGROUND: Spasticity is a common, serious symptom after stroke. Extracorporeal shock wave therapy (ESWT) has been suggested for the treatment of muscle spasticity. OBJECTIVE: To investigate the effects of ESWT on post stroke wrist flexor spasticity. METHODS: Fifteen patients with poststroke wrist flexor spasticity (12 male and 3 female with a mean age of 54 years) were enrolled. Patients received 1 sham ESWT followed by 1 active ESWT 1 week later. The outcome measures were the Modified Modified Ashworth Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…This resulted in mean differences showing clinical improvement in spasticity between pre-and postinterventions at Δ=34.97%. This comparison indicates the similar clinical effect in spasticity reduction for both ESWT modalities (Δ=0.52%), though slightly better for rESWT, however statistically non-significant for M0 (p=0.153), M1 (p=0.223), and M1-M0 (p=0.525) 54,[65][66][67][68][69]74 (Figure 2 and Table 1).…”
Section: Summary Of Mas Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…This resulted in mean differences showing clinical improvement in spasticity between pre-and postinterventions at Δ=34.97%. This comparison indicates the similar clinical effect in spasticity reduction for both ESWT modalities (Δ=0.52%), though slightly better for rESWT, however statistically non-significant for M0 (p=0.153), M1 (p=0.223), and M1-M0 (p=0.525) 54,[65][66][67][68][69]74 (Figure 2 and Table 1).…”
Section: Summary Of Mas Resultsmentioning
confidence: 73%
“…For purposes of the systematic review, the selected clinical outcomes were analyzed and compared between the baseline (M0) and the first measurement time point after ESWT (M1). The following outcomes were analyzed: (1) spasticity level as Δ% of grade in MAS or MMAS tools in 16 studies (nine studies in fESWT vs 7 studies in rESWT), 54,[61][62][63][64][65][66][67][68][69][70][71][72][73][74] (2) range of motion as Δ% of degree in GOM assessment of nine studies (six studies in fESWT vs three studies in rESWT), 54,63,64,67,68,70,72,75 and (3) selected electrophysiological parameters in such as MNC-V as Δ% of ms, CMAP-L as Δ% of ms, CMAP-A as Δ% of mV, FW-L as Δ% of ms, FW-A as Δ% of μV, HR-L as Δ% of ms and H/M-R as Δ% in six studies (four studies in fESWT vs two studies in rESWT), 65,67,70,73,75 It should be also noted that follow-up observations were undertaken in 12 studies within a mean period of 5.5 weeks (6.2 weeks in fESWT vs 4.7 weeks in rESWT) 54,[62][63][64][65][66]68,70,73 (Table 1).…”
Section: Outcome Measurements For Shock Wavesmentioning
confidence: 99%
“…Several previous studies that applied ESWT to patients with post-stroke muscle spasticity showed different results through various assessments [8][9][10][11][12][13][14][15][16]. The reason for the differences in the results was assumed to be the differences in the mechanisms of shock wave generation, energy per unit area, the number of applications, site of application, and patients' duration of illness [14].…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal shock wave therapy (ESWT) is a physical modality that has been used for various musculoskeletal problems [5][6][7]. Several studies have applied ESWT to patients with poststroke spasticity [8][9][10][11][12][13][14][15][16]. A few authors proposed that direct effect of ESWT on connective tissue stiffness and muscle fibrosis is the main mechanism for its effects on spasticity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Effective spasticity treatment will likely increase their functioning and their health-related quality of life. Clinical studies [43][44][45] have shown that ESWT may improve the muscle spasm of stroke patients without serious adverse reactions. Many studies conducted in recent years have been investigating the biological effects of ESWT.…”
Section: Discussionmentioning
confidence: 99%